Penerapan Model Pembelajaran Discovery Learning dalam Pembelajaran PAI di SMAN 3 Muaro Jambi - Mega Andika Putri (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research is motivated by the less-than-optimal implementation of the Discovery Learning model by educators. The aim of this study is to describe how Islamic Religious Education (PAI) teachers apply the Discovery Learning model in PAI subjects and to identify the obstacles faced by PAI teachers in its use in grade XI at SMAN 3 Muara Jambi. This issue was investigated using a descriptive qualitative method, which aims to analyze events, social activities, actions, beliefs, and thought patterns both individually and in groups. Data were collected through observation, interviews, and documentation. The research findings indicate that the implementation of the Discovery Learning model in PAI teaching has not been fully effective and has several shortcomings. The model consists of six stages: stimulation, problem identification, data collection, data processing, verification, and conclusion. However, these stages have not been fully carried out by students as expected. The challenges faced by teachers include low student motivation, lack of active participation, poor student discipline, and limited class time allocation.